Analisis Dampak Instrumen Asesmen Tidak Mengakomodasi Perbedaan Gaya Belajar Siswa Dalam Pembelajaran Matematika - Reza Oktiana Akbar; Triana Citra Lestari; Budi Manfaat (Journal on Education, 2024)
Abstract This research aims to analyze the impact of implementing assessments that do not consider differences in student learning styles in mathematics learning. The method used is an experiment with a quasi-experimental design. Students in two different class groups were randomly selected. The experimental group received an assessment that took learning style into account, while the control group received an assessment without considering this. The results of data analysis show that the learning outcomes of students who do not receive learning style-based assessments are not as optimal as those of students who receive learning style-based assessments (p < 0.05). These findings highlight the importance of considering students' learning styles in the assessment process to improve the effectiveness of mathematics learning. Analysis of questionnaires related to student perceptions of learning style-based assessments shows varying results. The overall indicator scores show variation in students' perceptions of mathematics assessments, with a fairly wide range of scores. Most students feel motivated to learn by implementing learning style-based assessments in mathematics assessments. However, some students experience limitations in developing their potential with learning style-based assessments. These findings provide valuable insight into diverse student perspectives on the use of learning style-based assessments in mathematics learning contexts.